From tension to cooperation: the interactions of british orientalists with indian scholars in Calcutta, 1784-1794 - Claire Gallien (Theatrum Historiae)
This paper aims at reconfiguring the production of Orientalist knowledge by focusing on the relationships between British and Indian scholars in India at the end of the eighteenth century. More particularly, I will analyze a discursive ambivalence that can be traced in Sir William Jones’s private letters (1784-1794), when the Orientalist referred to his work with native partners. Indeed, Jones described scenes of confrontations, while at the same time revealing moments of hospitality and conviviality. Such professional encounters were based on trust, and could even lead to friendship. This understanding of the construction of an Orientalist discourse that would accommodate the voice of the Indian other ultimately questions the depiction of Orientalism as a hegemonic discourse.